The Power of Politeness Strategies in EFL Student-Teacher Interaction: Teacher’s Gender Perspective - Febriansyah, Riyan; Munir, Ahmad; Anam, Syafiul; Setiawan, Slamet (IJET (Indonesian Journal of English Teaching), 2021)
This study aimed to investigate the use of politeness strategies in male and female teachers’ classrooms. Since the nature of student-teacher interaction was often influenced by the teachers’ actions and utterances, it was necessary to investigate the politeness based on the teachers’ gender perspectives, where those interactions could sometimes be felt as eitherthreatening or enjoyable. Investigating how male and female teachers’ politeness resulted in enjoyable student-teacher interaction differently, to empower the EFL classroom, this study also elaborated how the power of politeness strategies maximizes the EFL student-teacher interaction. The participants are several teachers and students who conduct the English Intensive Course Program in an undergraduate university, where they interact using English during the classes. In addition, this research followed a qualitative research design and used observation to collect data. Applying Brown and Levinson’s theory of politeness, the results show that politeness strategies bring a lively and friendly atmosphere during the classroom interaction. Specifically for female teachers who mostly use positive politeness strategies, they build more interaction with the students than male teachers. Positive politeness strategy focused on the students’ positive face by expressing the number of utterances that the students want to be listened to. It keeps students to have willingness to communicate so that the student-teacher interaction in the EFL classroom can be maximized